Retropubic, laparoscopic and mini‑laparoscopic radical prostatectomy: a prospective assessment of patient scar satisfaction - Quattrone, C (2015)
PURPOSE: To compare patient scar satisfaction after retropubic, standard laparoscopic, mini-laparoscopic (ML) and open radical prostatectomy (RP). METHODS: Patients undergoing RP for a diagnosis of localized prostate cancer at a single academic hospital between September 2012 and December 2013 were enrolled in this prospective nonrandomized study. The patients were included in three study arms: open surgery, VLP and ML. A skin stapler was used for surgical wound closure in all cases. Demographic and main surgical outcomes, including perioperative complications, were analyzed. Surgical scar satisfaction was measured using the Patient and Observer Scar Assessment Questionnaire (POSAS) and the two Body Image Questionnaire (BIQ) scales, respectively, recorded at skin clips removal and either at 6 months after surgery. RESULTS: Overall, 32 patients were enrolled and completed the 6 month of follow-up. At clips removal, laparoscopic approaches offered better scar result than open surgery according to the POSAS. However, at 6 months, no differences were detected between VLP and open, whereas ML was still associated with a better scar outcome (p = 0.001). This finding was also confirmed by both BIQ scales, including the body image score (ML 9.8 ± 1.69, open 15.73 ± 3.47, VLP 13.27 ± 3.64; p = 0.001) and the cosmetic score (ML 16.6 ± 4.12, open 10 ± 1.9, LP 12.91 ± 3.59; p = 0.001). Small sample size and lack of randomization represent the main limitations of this study. CONCLUSIONS: ML RP offers a better cosmetic outcome when compared to both open and standard laparoscopic RP, representing a step toward minimal surgical scar. The impact of scar outcome on RP patients' quality of life remains to be determined.